ASSOCIATION BETWEEN 25-HYDROXYVITAMIN D LEVELS AND GROWTH PARAMETERS IN THALASSEMIA WITH REPEATED BLOOD TRANSFUSION - Najma Khairani Harahap; Mulyono Mulyono; Yetty Movieta Nency; Nyoman Suci Widyastiti (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background. Blood transfusion is a therapeutic choice for thalassemia with anemia. Hemosiderosis is the side effects of blood transfusions which cause impaired liver function, leads to low vitamin D levels in plasma. The low level of vitamin D cause delay in physical growth. The aim is to determine the relation between 25-hydroxyvitamin D levels and growth parameters in thalassemia with repeated blood transfusion history. Method. In this analytical cross-sectional study, thalassemia patients with repeated blood transfusion and ages 0-18 years old were recruited. This research was held in Semarang, Purwodadi, and Rembang from May to September 2019. Thalassemia patients who met the criteria were measured the 25-hydroxyvitamin D level, physical activity and the growth parameters (weight, height, and body mass index). Results. Forty thalassemia patients aged 6-18 years old were recruited in this study. The percentage of boys are 47.5% and girls are 52.5%. Most of subject had high ferritin serum (87.5%) and low vitamin D level (87.5%). Growth parameters from the patients were 52.5% weight-for-age <5 percentile, 45% height-for-age <5 percentile and 25% BMI-for-age underweight. There isn’t significant result in 25-hydroxyvitamin D with growth parameters, and a significant result between physical activity and height-for-age (p=0.027), but not with weight-for-age and BMI-for-age. Conclusion. The 25-hydroxyvitamin D do not associate with growth parameters significantly in thalassemia with repeated blood transfusion but physical activity has significant association with height-for-age.